Gut Feminism - Wilson, Elizabeth A. (Elizabeth Ann), 1964- (Book collections on Project MUSE., 2015)
"In Gut Feminism Elizabeth A. Wilson urges feminists to rethink their resistance to biological and pharmaceutical data. Turning her attention to the gut and depression, she asks what conceptual and methodological innovations become possible when feminist theory isn't so instinctively antibiological. She examines research on anti-depressants, placebos, transference, phantasy, eating disorders and suicidality with two goals in mind: to show how pharmaceutical data can be useful for feminist theory, and to address the necessary role of aggression in feminist politics. Gut Feminism's provocative challenge to feminist theory is that it would be more powerful if it could attend to biological data and tolerate its own capacity for harm"--The publisher.